Description of the implementation of complementary therapy in midwifery services in Surabaya, Indonesia - Annisa' Wigati Rozifa; Nova Elok Mardliyana; Irma Maya Puspita (Majalah Obstetri & Ginekologi, 2023)
HIGHLIGHTS Midwifery services are carried out by combining conventional and complementary midwifery services Types of complementary therapies applied by 52% of independent midwifery services in Surabaya consisted of aromatherapy, hypnotherapy, herbal medicine, baby massage and spa, maternity massage, oxytocin massage, and yoga.   ABSTRACT Objectives: This study aimed to describe the implementation of complementary therapy among the independent midwifery practices in Surabaya, Indonesia. Materials and Methods: Employing a quantitative approach with a survey methodology, this study involved data collection through surveys administered to independent midwives practicing in Surabaya and midwives affiliated with independent midwifery practices. The questionnaires were containing the characteristics of the participants, the implementation of complementary therapies, and the complementary therapies integrated into the practice settings. Results: The findings revealed that 25 midwives (comprising 52%) provided complementary midwifery services, whereas 23 midwives (comprising 48%) abstained from incorporating complementary midwifery services into their independent midwifery practices. The types of complementary therapies implemented consisted of aromatherapy, hypnotherapy, herbal medicine, baby massage and spa, maternity massage, oxytocin massage, and yoga. Conclusion: This study concluded that 52% of independent midwives in Surabaya applied complementary therapy into their practices.